2011
DOI: 10.1182/blood.v118.21.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Viral Vector Mediated Gene Transfer for Hemophilia B

Abstract: 5 Background: Hemophilia B (HB), an X-linked bleeding disorder, is ideally suited for gene therapy. We investigated a novel approach using peripheral vein infusion of a single dose of a serotype-8 pseudotyped self-complementary adeno-associated virus (AAV) vector expressing a codon-optimized coagulation factor IX (FIX) transgene (scAAV2/8-LP1-hFIXco). Methods: Six severe HB subjects (FIX ≤1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Most studies are forced to exclude patients with detectable levels of NABs to AAV, as it is expected they will not benefit from the gene therapy. Even then, AAV clinical studies for hemophilia showed that seronegative subjects developed transaminase elevations weeks after AAV administration, which in some patients was concomitant with a rise in AAV capsid-specific CD8+ cells and the loss of transgene expression (Manno et al, 2006;Mingozzi et al, 2007;Nathwani et al, 2011). In the SMA study in which AAV9 was given IV at high dose, asymptomatic elevation of transaminases was observed in some of the newborn subjects, who fortunately responded to prednisolone treatment (Mendell et al, 2017).…”
Section: Host Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Most studies are forced to exclude patients with detectable levels of NABs to AAV, as it is expected they will not benefit from the gene therapy. Even then, AAV clinical studies for hemophilia showed that seronegative subjects developed transaminase elevations weeks after AAV administration, which in some patients was concomitant with a rise in AAV capsid-specific CD8+ cells and the loss of transgene expression (Manno et al, 2006;Mingozzi et al, 2007;Nathwani et al, 2011). In the SMA study in which AAV9 was given IV at high dose, asymptomatic elevation of transaminases was observed in some of the newborn subjects, who fortunately responded to prednisolone treatment (Mendell et al, 2017).…”
Section: Host Responsementioning
confidence: 99%
“…Currently utilized clinical strategies to side step or overcome immune concerns brought on by AAV gene therapies include the exclusion of patients with elevated anti-AAV antibodies from enrolling in clinical trials, administering in compartments that are thought to be immune privileged, including short-term immunosuppression regimens (e.g., oral prednisone; Mendell et al, 2017;Nathwani et al, 2011), or limiting the vector dose (Mendell et al, 2017). While these strategies have overall proven to be adequate in the ongoing clinical studies, it is clear they do not provide a solution for many of the outstanding concerns in the field.…”
Section: Host Responsementioning
confidence: 99%
“…Such doses increase the likelihood of inducing AAV vector-specific cytotoxic T-cell-mediated immune responses that could clear the gene-modified cells and cause acute liver toxicity. [17][18][19] However, this obstacle could potentially be overcome by using transient immune suppression. 19,20 Despite these potential immune complications, the use of a site-specific integrating AAV vector may overcome potential concerns of insertional oncogenesis given that that AAV is known to integrate at a low but measurable rate (0.1-1% transduction events).…”
Section: Hitting the Target Without Pulling The Triggermentioning
confidence: 99%
“…[17][18][19] However, this obstacle could potentially be overcome by using transient immune suppression. 19,20 Despite these potential immune complications, the use of a site-specific integrating AAV vector may overcome potential concerns of insertional oncogenesis given that that AAV is known to integrate at a low but measurable rate (0.1-1% transduction events). Nevertheless, with the exception of the emergence of hepatocellular carcinoma in neonatal mucopolysaccharidosis VII mice undergoing AAV gene therapy, 5 the overall oncogenic risk of using conventional AAV for gene therapy appears to be very low, 21 although this remains a largely unresolved issue.…”
Section: Hitting the Target Without Pulling The Triggermentioning
confidence: 99%
See 1 more Smart Citation